Development of Android-based Interactive Learning Media in Science Learning on Space Exploration Material - Ewin Suciana (JOURNAL EDUCATIONAL OF NURSING(JEN), 2024)
This study aims to develop The purpose of this study is to develop interactive learning media based on android in science learning on space exploration material. This study uses the Research and Development method with the ADDIE method which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subject of this study is the feasibility of interactive learning media and the object of this study is students. The feasibility test was carried out by means of individual tests (One to One) on 3 experts, namely material experts, learning experts, and media experts, as well as 3 students. In addition, small group tests were also conducted on 9 students selected based on good, moderate, and poor abilities in science subjects. The data collection technique was carried out using a questionnaire using a Likert scale. Data analysis was carried out using quantitative descriptive